Implementasi Pendekatan STEAM pada Mata Kuliah Bioteknologi Pangan Sebagai Upaya Mitigasi Learning Loss - Nur Fitriana Sam; Emilia Rahayu (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2022)
Engineering, Arts, and Mathematics) in the Food Biotechnology course to mitigate learning loss caused by the COVID-19 pandemic. This study used a qualitative approach. The unit of analysis was the students' biology education who took the Food Biotechnology course for the Academic Year 2020/2021. Researchers used direct observation techniques during sixteen meetings. In addition, interviews and document analysis were carried out to strengthen the data. The data were analyzed inductively through three stages (condensing data, displaying data, and making conclusions or data verification). The research showed that food biotechnology courses were integrated with several sciences. Technology integration occurred in the application of various methods of communication and online learning media. Engineering integration was when students practiced techniques, tools, and materials to produce new products. The integration of art was in food production and the application of product marketing strategies. The integration of mathematics was evident when students weighed and measured various cooking ingredients to match the dose, then calculated the profit and loss in sales. It appears that the students did not experience any learning loss. It implies that the STEAM approach in the learning process can reduce the risk of learning loss in students.